2005
DOI: 10.1016/j.eurpolymj.2004.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Permeation of water as a tool for characterizing the effect of solvent, film thickness and water solubility in cellulose acetate membranes

Abstract: Cellulose acetate membranes have been used in many applications; of particular interest are reverse osmosis systems, and as a neutral matrix for incorporation of different polymers (e.g., conducting polymers), inorganic ions (e.g., lanthanides) and organic (e.g., pharmaceutical) compounds. The properties of the new polymers derived from cellulose acetate or blends depend on those of cellulose acetate. This work presents an attempt to find links between thermodynamic and kinetic properties of cellulose acetate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 19 publications
4
21
0
Order By: Relevance
“…5 for all the TMCA series membranes. These values obtained were in accordance with the cited literatures [34,35], which was approximately 230 8C. It was observed that the melting point for the TMCA series membranes depend solely on CA and not MSG (although MSG was present in the dope solution and has T m of 232 8C).…”
Section: Separation Performancesupporting
confidence: 93%
“…5 for all the TMCA series membranes. These values obtained were in accordance with the cited literatures [34,35], which was approximately 230 8C. It was observed that the melting point for the TMCA series membranes depend solely on CA and not MSG (although MSG was present in the dope solution and has T m of 232 8C).…”
Section: Separation Performancesupporting
confidence: 93%
“…The decrease in the diffusion coefficient with the moisture content increase was also observed for a methylcellulose film or a cellulose acetate membrane, the decrease occurring from 3% (in d.b.) and 2% moisture content respectively, what is close to our values Valente, Polishchuk, Burrows, & Lobo, 2005). The shape of the curve could be explained by the mechanism of water migration in porous moist solids (Aguerre & Suarez, 2004).…”
Section: Kinetic (Diffusivity) Mechanism Of Water Vapour Transfer Thrsupporting
confidence: 84%
“…2 shows, as example, the infrared spectra of B1 and B4 films. In addition to the characteristic cellulose acetate bands at 1748, 1234 and 1046 cm À1 [25], new bands are observed at 1578 (C@C aromatic ), 2887 (C-H aliphatic ) and 3440 (N-H) cm À1 . These bands are indicative of the CP incorporation to cellulose acetate matrix.…”
Section: Film Characterizationmentioning
confidence: 92%